Dyslipidemia in Chronic Kidney Disease (Bangladesh Journal of Medical Biochemistry, 2024)
Globally chronic kidney (CKD) disease is one of the major health problems. Global prevalence of CKD is 8−16%. Prevalence of chronic kidney disease in Bangladesh is 26%. Patients with chronic kidney disease (CKD) exhibit significant alterations in lipoprotein metabolism. In this review different lipid parameters are shown from different studies and the pathogenesis of CKD induced dyslipidemia is discussed.Bangladesh J Med Biochem 2019; 12(2): 31-38